Biological indicators of lacustrine and alluvial soils in Venezuela under different land use. Part 1. Microbial activity and ecophysiological coefficient - Ruiz-Dager, Magaly; Paolini-Gomez, Jorge Emilio (REVISTA TERRA LATINOAMERICANA, 2021)
Land use can affect the activities of microorganisms and alter their biochemical transformations. This study examined basal respiration and ecophysiological coefficients in Venezuelan soils in Valencia Lake basin, under three different uses: natural vegetation, sugar cane monoculture and banana monoculture with the aim of determining the influence of land use on soil biological properties. Total organic carbon (Corg), water soluble carbon and basal respiration or microbiological activity showed a significant decrease, both in alluvial and lacustrine soils, when agricultural soils were compared with those of native vegetation. The metabolic quotient (qCO2) showed differences with relation to land use with higher values in the agroecosystems under banana trees according to the sequence in decreasing order: banana > natural vegetation > sugar cane. Nevertheless, the metabolic efficiency quotient (qCO2 /Corg) was significantly lower (P < 0.05) in soils under natural vegetation and showed the relationship between the most efficient carbon use and the nature of the available organic matter in these soils. These results reveal that both type of crop and agricultural practices exert an important influence on soil biological activity.